GENETIC PARAMETERS IN RIPARIAN REFLORESTATION WITHOUT STRUCTURE OF PROGENIES BY MIXED MODELS (REML/BLUP) - Silva, Alexandre Marques da [UNESP]; Oliveira Canuto, Daniela Silvia de [UNESP]; Teixeira de Moraes, Mario Luiz [UNESP] (Univ Federal Lavras-ufla, 2017)
The objective of this work is to estimate genetic parameters for silvicultural traits in riparian reforestation at 20 years of age, without progeny structure by mixed models (REML / BLUP). The present work was carried out at the Fazenda de Ensino, Pesquisa e Extensao (FEPE) of the Faculdade de Engenharia de Ilha Solteira, Universidade Estadual Julio de Mesquita Filho (FEIS/UNESP), located in the municipality of Selviria (MS). In February and March of 1986 began the planting of the riparian reforestation in modules, existing two Modules with different numbers of species. The spacing used in the planting of the species was 2 x 3 m. The riparian reforestation has an area of 9.5 ha in the total sum of the two Modules of planting. The silvicultural traita evaluated at 20 years were total plant height (ALT, m), diameter at breast height (DBH, cm) and survival of planted individuals, which were used to calculate the variance component components of genetic parameters, using the genetic-statistical program SELEGEN-REML/BLUP. High genetic variability was observed among the genotypes for the silvicultural traits studied in the riparian reforestation. The accuracy was of high magnitude, showing good reliability of the results. The mixed model method (REML/BLUP) was adequate for the estimation of genetic parameters and prediction of genotypic values in riparian reforestation, and it could be used routinely.
Keywords: Multivariate analysis; Genotypic divergence; Conservation